The Effect of Madrasah Principal Leadership and Compensation on Teacher Job Satisfaction - Syamsuddin Syamsuddin; Bahaking Rama; Baharuddin Baharuddin; Andi Achruh; Danial Rahman (FITK UIN Walisongo, 2022)
This research was designed to examine and evaluate the influence of the principal leadership and the provision of compensation on teacher job satisfaction at Madrasah Aliyah Negeri in the Sinjai Regency. This study used a quantitative approach with the ex-post facto method. One hundred twenty-three respondents in this study were madrasah (Islamic schools) teachers. The results indicated that headmaster leadership and the arrangement of compensation have a positive and significant effect on teacher job satisfaction, both partially and simultaneously. Thus, the level of job satisfaction felt by teachers in an educational institution depends on the efficiency of the leadership applied and the provision of adequate compensation. Therefore, educational institutions must pay attention to implementing effective leadership and a good compensation system to create teacher job satisfaction. So, they are excited to perform their roles optimally.